Counter-ideological forces of “Mr Gate” in online journalism in Malaysia: a study of MalaysiaKini and The Malaysian Insider - Kasmani, Mohd Faizal; Sabran, Rosidayu; Othman, Siti Suriani; Ramle, Noor Adzrah (2017)
The online news media are said to have changed the understanding of the gatekeeping theory. Due to the virtually unlimited news space together with the interactivity in the online presentation of news, the Internet defies the whole conception of gate keeping in journalism.This article seeks to examine the influence of gatekeeping forces in two influential Malaysian online news portals, MalaysiaKini and The Malaysian Insider (TMI), during the 2013 Malaysian general election. Based on the hierarchical model of news conception, this study assessed the influence of ideological gatekeeping forces on their news content.The reporting by both news portals was subjected to qualitative textual analysis.The results are triangualted with interviews with corresponding reporters and editors from MalaysiaKini and TMI. The findings show that although the reporting of MalaysiaKini and TMI is counter-ideological, the gatekeeping process remains intact. This is due to the speed factor and the requirement of the news portals to abide by the media-related laws in Malaysia.